2021
DOI: 10.1159/000514821
|View full text |Cite
|
Sign up to set email alerts
|

Multigene Combined Detection by RT-qPCR Using Cytological Specimens

Abstract: <b><i>Objective:</i></b> The aim of the study was to investigate the mutation status of multiple driver genes by RT-qPCR and their significance in advanced lung adenocarcinoma using cytological specimens. <b><i>Materials and Methods:</i></b> 155 cytological specimens that had been diagnosed with lung adenocarcinoma in the Fourth Hospital of Hebei Medical University were selected from April to November 2019. The cytological specimens included serous cavity effusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The same group also reviewed the best cytologic techniques for this kind of analysis and showed that fresh samples obtained by membrane cell collector method had better performance than cell blocks, probably due to the avoidance of contaminants that can hinder DNA or RNA extraction. 87 Sgariglia et al also showed the feasibility of performing multiplex digital color-coded barcode techniques (nCounter) for RNA detection in cytological samples with a 48-gene panel to improve the detection rate. 88…”
Section: Multiplex Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group also reviewed the best cytologic techniques for this kind of analysis and showed that fresh samples obtained by membrane cell collector method had better performance than cell blocks, probably due to the avoidance of contaminants that can hinder DNA or RNA extraction. 87 Sgariglia et al also showed the feasibility of performing multiplex digital color-coded barcode techniques (nCounter) for RNA detection in cytological samples with a 48-gene panel to improve the detection rate. 88…”
Section: Multiplex Assaysmentioning
confidence: 99%
“…These authors confirmed similar results with both types of samples and, although the most prevalent molecular abnormalities involved EGFR , ALK and ROS1 , as expected, they retrieved a small number of abnormalities in other genes that are amenable to targeted inhibition. The same group also reviewed the best cytologic techniques for this kind of analysis and showed that fresh samples obtained by membrane cell collector method had better performance than cell blocks, probably due to the avoidance of contaminants that can hinder DNA or RNA extraction 87 . Sgariglia et al also showed the feasibility of performing multiplex digital color‐coded barcode techniques (nCounter) for RNA detection in cytological samples with a 48‐gene panel to improve the detection rate 88 …”
Section: Molecular Markers In Lung Nsclcmentioning
confidence: 99%